Asset market linkages in crisis periods - Philipp Hartmann; Stefan Straetmans; Casper de Vries (European Central Bank (ECB), 2001)
We characterize asset return linkages during periods of stress by an extremal dependence measure. Contrary to correlation analysis, this non-parametric measure is not predisposed towards the normal distribution and can account for non-linear relationships. Our estimates for the G-5 countries suggest that simultaneous crashes in stock markets are about two times more likely than in bond markets. Moreover, stock-bond contagion is about as frequent as flight to quality from stocks into bonds. Extreme cross-border linkages are surprisingly similar to national linkages, illustrating a potential downside to international financial integration
Keywords: G1; F3; C49; 330; Bivariate Extreme Value Analysis; Extreme Co-movements; Flight to Quality